2022
DOI: 10.15407/ujpe67.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cross-Section in the Presence of a Weak Laser Field for Inelastic Scattering

Abstract: The objective of this work is to study the differential cross- section in the presence of a weak laser field (visible and UV) in the case of inelastic scattering. When the target absorbs the energy, the differential cross section increases, according to the theoretically constructed model. The differential cross-section initially decreases to a minimum and finally takes a maximum value, when the target emits the energy. The energy emission occurs at 5 eV, 10 eV, 13 eV, 16 eV, 20 eV, 25 eV, and 30 eV. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Dhobi et al study the differential cross-section in the presence of a weak laser field (visible and UV) in the case of inelastic scattering and found that DCS initially decreases to a minimum and finally takes a maximum value, when the target emits the energy of 5 eV, 10 eV, 13 eV, 16 eV, 20 eV, 25 eV, and 30 eV. In addition, the differential cross-section also increases with the scattering angle [16]. Also for the scattering of DCS in weak field Dhobi et al design the hamitonian to study the DCS around the proton exchange membrane which is futre work for this team and work is in progress [17] Yadav et al study the DCS with elliptically polarized beam e-H scattering in high intensity with target energy below eV in presence of coulomb potential.…”
Section: Resultsmentioning
confidence: 99%
“…Dhobi et al study the differential cross-section in the presence of a weak laser field (visible and UV) in the case of inelastic scattering and found that DCS initially decreases to a minimum and finally takes a maximum value, when the target emits the energy of 5 eV, 10 eV, 13 eV, 16 eV, 20 eV, 25 eV, and 30 eV. In addition, the differential cross-section also increases with the scattering angle [16]. Also for the scattering of DCS in weak field Dhobi et al design the hamitonian to study the DCS around the proton exchange membrane which is futre work for this team and work is in progress [17] Yadav et al study the DCS with elliptically polarized beam e-H scattering in high intensity with target energy below eV in presence of coulomb potential.…”
Section: Resultsmentioning
confidence: 99%
“…They discovered that DCS initially drops to a low value before achieving its maximum level when the target emits the energy. In addition, the DCS also increases with the scattering angle [11].…”
Section: Introduction mentioning
confidence: 96%